(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
According to the findings, the rahata region has access to generally clean ground water thatmay be used for agriculture. The quality of ground water has been suggested for little improvement andproper management. Monitoring water quality in a variety of situations is important for ensuring thepublic’s health and safety since human activities, such as the use of pesticides and chemical fertilizers,may have an adverse effect on the natural quality of ground water. Water is an amazing material due toits unique ability to dissolve and transport a broad variety of compounds in suspension. The possibilityof contamination exists. In spite of water’s central role in maintaining life on Earth, it is the one naturalresource that has suffered the most from human activity, both in terms of quality and quantity. The goalof this investigation is to identify the characteristics of the ground water in the area. Finally, we addressthe local water status, soil type, and other pertinent issues as they relate to ground water augmentationas a means of providing sustainability to ground water development in rahta tehsil. We also talk aboutwater and its unique characteristics.